One Religion, Different Readings: (Mis)interpretations of Korean Buddhism in Colonial Korea, Late 1920s-Early 1930s - Tikhonov (Pak Noja), Vladimir (2010)
In colonial Korea (1910–1945), Buddhism’s sheer resilience and popularity drew attention of the Japanese colonial scholars, who initiated in the 1910s–1920s what they viewed as “scientific” study of Korean Buddhism. The attempts at “scientification” of Korean Buddhism research—exemplified by Keijō Imperial University professor Takahashi Tōru (1878–1967), also known for his research on Korean oral literature and Confucian philosophy—undoubtedly broadened the scope of academic inquiry and contributed to systemization of materials on Korean Buddhist history. However, the “scientism” of the colonial scholars was from the very beginning tarnished by their Orientalist attitudes. They viewed Korean Buddhism as “slavishly dependent” upon Chinese tradition and Korean state authorities. These colonialist attitudes provoked a heated nationalist response. Prominent “cultural nationalists”, such as Ch’oe Namsŏn (1890–1957), reacted by painting a picture of East Asia’s ancient Buddhist tradition with Korea in its centre. This picture, its visible shortcomings notwithstanding, eventually laid the fundament for the nationalist view of Korean Buddhist history in post-1945 South Korea.
Keywords: nationalism [End Page 163]; Orientalism; Takahashi Tōru; Ch’oe Namsŏn; Korean Buddhism